Geological and paleoclimatic events reflected in phylogeographic patterns of intertidal arthropods (Acari, Oribatida, Selenoribatidae) from southern Japanese islands. (24th May 2021) - Pfingstl, Tobias; Wagner, Maximilian; Hiruta, Shimpei F.; Bardel‐Kahr, Iris; Hagino, Wataru; Shimano, Satoshi
Abstract: A comprehensive study of the intertidal oribatid mite fauna of southern Japanese islands revealed the presence of the selenoribatid Arotrobates granulatus Luxton, 1992 and two yet undescribed species. The latter are herein described as Indopacifica taiyo n. sp., occurring from the Southern to the Central Ryukyus, and Indopacifica tyida n. sp., which was only found on the most western island of the Ryukyus, namely Yonaguni. A concomitant molecular genetic study using mitochondrial COI and 18S rRNA gene sequences, demonstrated that the phylogeographic pattern of I. taiyo n. sp. reflects recent expansion on the Southern and Central Ryukyus, probably due to existing land bridges during the late Pleistocene. Arotrobates granulatus, on the other hand, shows three distinct lineages, one on Japanese mainland, another on the island of Amami, and the third on part of the Central and Southern Ryukyus. These lineages are most likely the result of the break‐up of a large peninsula reaching from China to the Northern Ryukyus about 1.2–1.7 million years ago. Despite emerging land bridges in the late Pleistocene, this species was not able to expand its range again which indicates very low dispersal abilities. Morphometric data of I. taiyo n. sp. show considerable intraspecific variation between island populations correlating with geography. This found variation is suggested to be a result of phenotypic plasticity caused by diverging local environmental factors. From an ecological perspective, all three found species are classified as intertidal rock‐dwellers feeding on diverse algae, whereas I. taiyo n. sp. and Arotrobates granulatus occasionally occur in mangrove habitats. Abstract : We found two new species of intertidal oribatid mites, Indopacifica taiyo n. sp. and Indopacifica tyida n. sp., on coasts of the southern Japanese islands. Molecular genetic data indicate that the Tokara gap has acted as an effective biogeographic barrier for these and other organisms. The phylogeographic pattern of I .  taiyo n. sp. also reflects recent expansion on the Southern and Central Ryukyus, probably due to existing land bridges during the late Pleistocene. Zusammenfassung: Eine umfangreiche Studie der litoralen Hornmilbenfauna der südlichen japanischen Inseln zeigte das Vorkommen von Arotrobates granulatus und zweier bisher unbeschriebener Arten. Diese werden hier beschrieben als Indopacifica tayio n. sp., welche von den südlichen bis zu den zentralen Ryukyus vorkommt, und als Indopacifica tyida n. sp., welche nur auf der Insel Yonaguni gefunden wurde. Eine begleitende molekulargenetische Studie der mitochondrialen COI und 18S rRNA Gensequenzen zeigte, dass das phylogeographische Muster von Indopacifica taiyo n. sp. eine rezente Ausbreitung auf den südlichen und zentralen Ryukyus widerspiegelt, die vermutlich durch, während des späten Pleistozäns bestehender, Landbrücken möglich war. Arotrobates granulatus hingegen zeigt drei klar getrennte Linien, eine auf dem japanischen Festland, eine andere auf der Insel Amami, und eine dritte auf Teilen der zentralen und südlichen Ryukyus. Diese Linien sind vermutlich ein Resultat des Zerfalls einer großen Halbinsel, die vor ca. 1.2‐1.7 Millionen Jahren von China bis zu den nördlichen Ryukyus reichte. Trotz der vorübergehenden Landbrücken im späten Pleistozän, war es dieser Art nicht möglich sich wieder auszubreiten, was auf ein geringes Verbreitungspotential hinweist. Morphometrische Daten von Indopacifica taiyo n. sp. zeigen erhebliche intraspezifische Variation zwischen den Populationen verschiedener Inseln, welche stark mit der Geographie korreliert. Vermutlich ist diese Variation eine Folge phänotypischer Plastizität, verursacht durch sich unterscheidende lokale Umweltfaktoren. Vom ökologischen Standpunkt aus, können alle drei gefundenen Arten als litorale Felsbewohner eingestuft werden, die verschiedene Algen fressen, wobei Indopacifica taiyo n. sp. und Arotrobates granulatus gelegentlich auch in Mangroven vorkommen können.